Assuring the quality of VET systems by defining expected outcomes : a cross-country analysis in seven Member States - (:unkn) unknown (Office for Official Publications of the European Communities, 2008)
"The purpose of the study was to investigate how targets and standards are set for the system as a whole, for the providers and for the individual learners in seven countries: Denmark, Germany, Ireland, France, Italy, the Netherlands and the United Kingdom. The main targets (outcome standards) at system level may be set in the annual Finance Act, public service agreements or by defining basic performance levels. The specific targets concern students' and adults' achievements, dropout rates, participation rates, diploma or qualification rates, satisfaction rates or employability rates. The main targets (outcome standards) for providers are floor targets relating to accreditation, criteria and parameters concerning self-evaluation and external evaluation and voluntary targets, such as success rate and grades. Outcome standards for individual learners are set as part of the different national qualifications frameworks or region-specific standards - either by parliaments and ministries, national technical authorities, regional political authorities or in consultation with the social partners." (Herausgeber)
Keywords: L 6.2 Qualitätsmanagement/Qualitätssicherung; S 2.2.5 Standards in der beruflichen Bildung; L 6.2.3 Evaluation; T 3 Forschungsmethoden; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; Qualität; Qualitätssicherung; Input-Output-Analyse; Indikatoren; Evaluation; Berufsbildungssystem; Empirische Untersuchung; Internationaler Vergleich; Frankreich; Italien; Vereinigtes Königreich; Irland; Bundesrepublik Deutschland; Niederlande; Dänemark